THE CONCEPT OF WASATHIYAH IBN TAIMIYYAH AND ITS IMPLEMENTATION IN AQIDAH - Syamsuddin Arif; Nurhadi Ikhsan; Syaiful Ulum (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2019)
In recent decades groups emerged in the name of the Islamic Group and claimed that their group was the most righteous and followed the Prophet in the case of aqidah, worship and Mu'amalah, while they were not aware that they fell into excessive (Ghuluw) both ghuluw in Aqidah , worship and Mua’malah, among the reasons is wrong in placing (Fiqh Tanzil) which distinguishes between the principal (Usul) and the branch (Furu’). While on the other hand there also emerged groups who claimed to be the most moderate (Wasath), Tolerant to the point of being too far and they fell into disparaging (tafrit) so that they sacrificed things that were in principle (aqeedah). Moderation (Washatiyyah) is also often misunderstood in its meaning and implementation, and it is not uncommon for certain groups to claim punishment for someone or other groups as radical or extreme. This study focuses on the first two issues relating to the Washatiyyah concept in Aqeedah and the analysis and criticism of extremism in aqeedah. the second is the determination of Standardization of wasathiyyah and wasathiyah methodology so that not only any group can claim that he and his group are the most moderate (wasath). And the most accurate implementation of wasathiyyah is on the subject of Shirk and in this case Ibn Taimiyyah is the most authoritative figure to be the Source of Reflections in the aqidah as well as the standard in wasathiyyah as he explains in his book